Functional screening of abundant bacteria from acidic forest soil indicates the metabolic potential of Acidobacteria subdivision 1 for polysaccharide decomposition - Lladó, Salvador; Žifčáková, Lucia; Větrovský, Tomáš; Eichlerová, Ivana; Baldrian, Petr (Biology and fertility of soils, 2016)
Coniferous forest soils have an indispensable ecological role in the global cycles of nutrients on Earth. Despite the fact that microbial communities in this ecosystem were subject of multiple studies, the involvement of individual taxa in the processes of organic matter transformation and the functional roles of dominant and active bacteria are largely unknown. Here, we have performed a comprehensive isolation effort to obtain multiple dominant bacterial taxa from a Picea abies forest soil and provide their physiological characterization. This information allows us to link ecological traits with groups of microorganisms. In the study, conventional culture techniques at acidic pH and low-nutrient content led to the recovery of 299 bacterial isolates. The isolates represented operational taxonomic units (OTUs) that contained 20 and 32 % of all bacterial genomes detected in the litter and soil by 16S amplicon analysis, including some of those bacterial strains representing the most abundant and active OTUs. These included also several isolates of the still underexplored phylum of the Acidobacteria, all of them belonging to the subdivision 1 of the phylum. Acidobacterial isolates produced the widest range of enzymes among all isolates and highest enzyme activities in acidic conditions. Moreover, members of the Acidobacteria represented more than 50 % of the isolates able to grow on disaccharides produced during the breakdown of cellulose, chitin, and starch. Our results indicate that Acidobacteria may play an important ecological role by degrading polysaccharides of plant and fungal origin in the important ecosystems of acidic coniferous forests.